Supersymmetric U(N) Chern-Simons-Matter Theory and Phase Transitions - Russo, Jorge Guillermo (2015)
We study N=2 supersymmetric U(N) Chern–Simons with Nf fundamental and Nf antifundamental chiral multiplets of mass m in the parameter space spanned by (g, m, N, Nf), where g denotes the coupling constant. In particular, we analyze the matrix model description of its partition function, both at finite N using the method of orthogonal polynomials together with Mordell integrals and, at large N with fixed g, using the theory of Toeplitz determinants. We show for the massless case that there is an explicit realization of the Giveon–Kutasov duality. For finite N, with N > Nf, three regimes that exactly correspond to the known three large N phases of the theory are identified and characterized.